The synthesis and identification of complete stacking bilayer MoS2 flakes with unconventional shapes via chemical vapor deposition. (October 2021) - Chen, Fei; Jiang, Xia; Shao, Jiaqi; Fu, Li; Zhao, Shichao; Su, Weitao
Abstract: Two-dimensional complete stacking bilayer molybdenum disulfide (MoS2 ) crystals with several unconventional morphologies, including four-point star, hexagon, rhomboid, trapezoid, and pentagon, have been attained by employing the space-confined chemical vapor deposition approach. The morphology, structure, and fundamental features of as-produced domains are systematically characterized via utilizing optical microscopy, atomic force microscopy, and Raman/PL system, elucidating bilayer feature of various MoS2 flakes. The variation of such various bilayer MoS2 crystals is discussed based on the difference of growth rate between different sides. Highlights: Complete stacking bilayer MoS2 flakes with various shapes have been attained via space-confined chemical vapor deposition. Evolution of varied shapes, layer-number, and optical properties of bilayer MoS2 flakes has been evaluated. Possible growth mechanism of these bilayer MoS2 flakes with various shapes has been discussed.